The Principal's Strategy in Implementing Permendikbud on Strengthening Character Education to Realize School Religious Culture - Fanti Agustina; Nunuk Hariyati; Amrozi Khamidi; Yatim Riyanto; Ayu Wulandari (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Character education, as an integral part of national education, faces serious challenges due to the impact of rapid digital technological advancement, which has led to a decline in students' character index, particularly in the aspects of independence and integrity. Religious culture in schools has emerged as a strategic approach to strengthen students’ spiritual and moral values. However, its implementation is still constrained by partial technical approaches and limited participation from the school environment and the wider community. This study aims to identify strategies employed by school principals in strengthening character education through religious culture at SMP Negeri 2 Sukodono, Sidoarjo. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentary studies. The findings reveal six key strategies: (a) integration of religious values into the curriculum, (b) modeling and exploration of values, (c) habitual religious practices, (d) collaboration with school committees and parents, (e) infrastructure adjustments, and (f) continuous evaluation. These findings support Dewey’s theory of habit formation and successfully address challenges such as student diversity and low parental involvement through inclusive approaches. Overall, the implementation of religious culture not only enhances students’ character but also fosters a harmonious school climate, contributing both theoretically and practically to the development of value-based leadership models and character education policies.